Abnormal Bone Mineral Maturation in the Chronic Uremic State - Russell, Jean E. (1973)
X-ray diffraction analysis of bone from chronically uremic but nonacidotic rats with normocalcemia and hyperphosphatemia revealed smaller apatite crystals and an increase in the X-ray amorphous mineral fraction when compared to age-matched, pair-fed control animals, indicating less advanced mineral maturation in the uremic animals. Studies in animals with varied degrees of chronic renal insufficiency revealed a progression of the bone crystal maturational defect with advancing uremia.